CO-SPECTRA OF JOINT SPECTRA OF STRUCTURES (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2004)
We introduce and study the notion of joint spectrum of finitely many abstract structures. A characterization of the lower bounds of the elements of the joint spectrum is obtained.